THE EFFECT OF USING SURVEY QUESTIONS READ RECITE REVIEW (SQ3R) LEARNING MODEL FOR LEARNING OUTCOMES IN MATHEMATICS STUDENTS OF SMP N 2 PLERET - Ika Putri Astriyana Sari; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was conducted on the ground of the learnings are applied during this tends to be teacher’s centered, many students who are less active, less enthusiastic in learning process. Therefore, it needs a learning model that involves many students makes a student more active. This research aims to determine the influence of the survey questions read recite review (SQ3R) learning model toward mathematics learning outcomes in class VIII of even semester in SMP N 2 PLERET of academic year 2015/2016. The populations in this research were students of class VIII A, B, C, D, E, F, G SMP N 2 Pleret. Samples were taken using random sampling techniques derived from class VIII G as an experimental class and class VIII A as the control class. The data collection method used was the test method. Testing instrument using validity test, remainder test, and reliability test. Data were analyzed using a prerequisite analysis test including normality test using Chi-Square formula, homogeneity test by test Bartlett, and hypothesis test with t-test. Based on calculations at the significant level   and 63 degrees of freedom, we conclude that : (1) there is a different result of math study that using  Survey Questions Read Recite Review (SQ3R) method and conventional. This is indicated by the result of the first test of the hypothesis that . (2)learning using Survey Questions Read Recite Review (SQ3R) learning model is more effective than learning using conventional. It is  shown on the second  test of the hypothesis that the test result .